Estudio de la valoración empresarial bajo el modelo eva para la empresa industrial prodicereal s.a. de la ciudad de Latacunga, provincia de Cotopaxi durante el período 2013 - Curay Pérez, Soraya Alexandra (2015)
Thesis project was developed in the “PRODICEREAL S.A.” company Latacunga city, which requires a business valuation, besides it needs to know the real value of the company, because it is not known, if the company generates higher value than those presented on Accounting Financial Statements, for that reason investigators propose to carry out a study of business valuation under model EVA (Economic Value Added); it is an economic indicator whose basic objective to measure the result of management economic activity through monetary expression, which requires a deeper analysis developed by traditional indicators revenue growth, earnings and actives like factors performance evaluation, therefore it proceeded to execution of the methodology chosen….